(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe some clinical features of pediatric patients with sequences of viral encephalitis treated at National Hospital of Acupuncture. Subjects and methods: Prospective descriptive study, conducted on 140 pediatric patients with sequences of viral encephalitis treated at National Hospital of Acupuncture from January 2022 to December 2023. Results: Clinical features of children with sequences of viral encephalitis are mainly moderate and severe: unrecognizable 73.57%; mumbled speech, with sounds but no sounds 71.43%; slow swallowing, only able to eat liquids 68.57%; sometimes incontinent urination and defecation 58.57%; increased salivation 5.71%; severe muscle tone disorders 73.57% and severe extrapyramidal disorders 67.86%. Average Liverpool score 38.39 ± 5.29. Average modified Ashworth score 3.15 ± 0.69. Average Henry score 4.22 ± 0.66. Average gross motor function score 4.16 ± 0.50. Conclusion: Children with sequences of viral encephalitis treated at National Hospital of Acupuncture have diverse clinical manifestations, the most common of which are disorders of consciousness, muscle tone disorders and language disorders. Fully identifying clinical features helps guide effective rehabilitation treatment, contributing to improving the quality of life for children.